Decarbonizing Freight Transport Acceptance and Policy Implications - Pfoser, Sarah (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2022)
This Open-Access-Book analyzes the acceptance of sustainable freight transport and suggests a new framework for policy measures to decarbonize freight transport. Despite intense political endeavors, the environmental performance of the transport system has not improved in the previous years. It seems that the existing measures are not sufficient to motivate transport users to implement sustainable freight transport strategies. The case of three different strategies for sustainable freight transport is studied: horizontal collaboration in a Physical Internet network, multimodal freight transport and liquefied natural gas (LNG) as alternative truck fuel. Each of these three strategies falls within a different pillar of the avoid-shift-reduce framework. The determinants of acceptance and suggested policy measures in this study reflect transport users' needs towards sustainable freight transport. This should support policy makers and the logistics industry to implement sustainable practices and achieve the ambitious emission targets by decarbonizing freight transport. About the author Sarah Pfoser is working as a senior researcher at the Logistikum Steyr, University of Applied Sciences Upper Austria. She obtained her doctoral degree from the University of Bremen in 2021. Her research is intended to promote sustainable innovation in the logistics industry. This includes not only freight transport, but also other areas such as transport packaging.